Estimating a time-varying distribution-led regime - Paul Carrillo-Maldonado; Michalis Nikiforos (Levy Economics Institute of Bard College, 2022)
This paper estimates the distribution-led regime of the US economy for the period 1947-2019. We use a time varying parameter model, which allows for changes in the regime over time. To the best of our knowledge this is the first paper that has attempted to do this. This innovation is important, because there is no reason to expect that the regime of the US economy (or any economy for that matter) remains constant over time. On the contrary, there are significant reasons that point to changes in the regime. We find that the US economy became more profitled in the first postwar decades until the 1970s and has become less profit-led since; it is slightly wage-led over the last fifteen years.
Keywords: E11; E12; C11; C3; 330; Wage-led; Profit-led; Distribution; Growth; Time-Varying Parameters (VAR)